Ibnu Ḥazm Al-Andalusī dan Khilāfah - Zuhri Zuhri (UIN Sunan Kalijaga Yogyakarta, 2016)
As a form of freedom of speech and establishing an organization, the discourse about the caliphate has lately resurfaced. As a concept, the caliphate began to appear after the prophetic era. This concept evolved somewhat in line with the dynamics of power and thought in Islamic world. This paper seeks to explore the ideas and dialectic courses of Ibn Hazm with the dynamics of the Islamic caliphate in Andalusia. He recorded historical facts, formulated theoretical outlines and plunge directly into the process of maintaining the caliph. Historical data of Caliphate transition either through “al-Khilafah” or succession and “al-Wilayah” or appointment, according to Ibn Hazm, must be based on the guiding principle of leadership (al-Imamate) in Islam. Ibn Hazm’s idea turned out to collide with the process of power transition, away from the ideal formulas he has composed. The reality of Ibn Hazm is the the tension between al-syari’ah and al-siyāsah.[Sebagai bentuk kebebasan berpendapat dan berorganisasi, perbincangan tentang khilafah kembali mengemuka akhir-akhir ini. Sebagai suatu konsep, khilafah mulai muncul pasca era kenabian. Konsep ini berkembang sedemikian rupa seiring dengan dinamika pemikiran dan kekuasaan dalam Islam. Paper ini berusaha mengeksplorasi gagasan dan pergulatan Ibnu Hazm dengan dinamika khilafah Islam di Andalusia. Ia merekam fakta-fakta historis, merumuskan langkah-langkah teoretis, dan terjun langsung ke dalam proses mempertahankan khalifah. Data-data historis peralihan kekhilafahan baik melalui al-khilāfah atau suksesi dan al-wilayah atau penunjukkan langsung, menurut Ibnu Hazm, harus didasarkan atas prinisp-prinsip kepemimpinan (al-Imāmah) dalam Islam. Gagasan Ibnu Ḥazm ini ternyata berbenturan dengan realitas proses peralihan kekuasaan yang jauh dari idealitas rumusan Ibn Ḥazm. Realitas Ibnu Ḥazm adalah realitas ketegangan antara al-syarī’ah dan al-siyāsah.]